Analisis Kepuasan Pengguna Jasa Transportasi Kereta Api - Yogi Indra Pramana; Gustami Harahap; Mitra Musika Lubis (Universitas Medan Area, 2019)
The purpose of this study is the for knowing the quality of services which include reliability, responsiveness, assurance, empathy, tangibles effect on user satisfaction services of PT Kereta Api Indonesia in Division 1 North Sumatra in the distribution of CPO and for knowing what variable most dominant influence on satisfaction of service users PT Kereta Api Indonesia Division 1 North Sumatra in the distribution of CPO. The sampling method was census method. Respondents in this study is a train service users in the process of distribution of CPO and samples taken between 5 respondents. The data collected are primary data and secondary data. The analytical method used is the analysis of linear regression. Based on the multiple linear analysis in a test based on the level of significance was obtained F count is equal to 5,487 with sig = 0.005. Because sig = 0.000 0.05 indicates that the quality of service simultaneously together or simultaneously have a strong influence (significant) to increase service user satisfaction.Â